Hard carbon negative electrode material and preparation method thereof, sodium ion battery negative electrode and sodium ion battery

A two-step carbonization process with a pore-forming agent increases pore content in hard carbon electrodes, addressing high energy consumption and enhancing sodium storage capacity in sodium ion batteries.

CN119160872APending Publication Date: 2024-12-20CHINA MINMETALS GRP (HEILONGJIANG) GRAPHITE IND CO LTD
View PDF 0 Cites 4 Cited by

Patent Information

Application Number
CN202411176892.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-26
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

Existing hard carbon negative electrode materials for sodium ion batteries require high temperatures for production, leading to high energy consumption and limited sodium storage capacity, while lower temperature alternatives lack optimal performance.

Method used

A two-step carbonization process involving preliminary carbonization at 200-800°C, acid washing to remove templates, and a second carbonization at 1000-1200°C, combined with the use of a pore-forming agent like zinc gluconate, to increase pore content and sodium storage sites in the hard carbon material.

Benefits of technology

The method enhances sodium storage capacity and efficiency, achieving reversible capacities up to 338 mAh/g with improved pore structure and sodium storage performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119160872A_ABST
    Figure CN119160872A_ABST
Patent Text Reader

Abstract

The invention provides a hard carbon negative electrode material and a preparation method thereof, a sodium ion battery negative electrode and a sodium ion battery. The preparation method comprises the following steps: S1, mixing a hard carbon precursor and a pore forming agent according to a mass ratio of 1: (0.1-5) to obtain a precursor mixed material; s2, the precursor mixed material is subjected to primary carbonization for 1-5 h at the temperature of 200-800 DEG C under protection of protective gas, and a primary carbonized material is obtained; s3, mixing the primarily carbonized material with an acid solution for 4-12 hours to obtain a template-removed material; and S4, carrying out second carbonization on the template-removed material at 1000-1200 DEG C for 1-5 hours to obtain the hard carbon negative electrode material. The hard carbon negative electrode material has excellent sodium storage capacity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of sodium ion batteries, and in particular to a hard carbon negative electrode material and a preparation method thereof, a sodium ion battery negative electrode, and a sodium ion battery. Background Art

[0002] Since the 21st century, fossil energy such as coal and oil has been decreasing, and the development of new energy industry is the general trend. Among them, alkali metal ion batteries such as sodium ion batteries and sodium ion batteries have the advantages of high energy density, safety and environmental protection. However, sodium ion batteries have a high demand for sodium ore, and the cost of raw materials such as sodium carbonate remains high. In contrast, the sodium ore resources required for sodium ion batteries are very abundant, and the production cost is relatively lower. It has broad development prospects in the fields of electric vehicles and energy storage.

[0003] The negative electrode material of sodium-ion batteries is usually a hard carbon material, which has a long platform in the low-pressure range and therefore has a higher energy density in the full battery. Its precursor source is wide, making it the most promising negative electrode material for sodium-ion batteries.

[0004] Hard carbon anodes are usually obtained by dehydrogenation, deoxidation and carbonization of biomass precursors, asphalt, resin and other precursors under high temperature inert atmosphere. Hard carbon materials with higher performance often require higher temperatures above 1300°C, which consumes a lot of energy. Hard carbon materials with excellent performance at lower temperatures such as 1100°C still need to be explored. Summary of the invention

[0005] In order to solve the above problems in the prior art, the present invention aims to provide a hard carbon negative electrode material and a preparation method thereof, a sodium ion battery negative electrode, and a sodium ion battery. The hard carbon negative electrode material has excellent sodium storage capacity.

[0006] In order to achieve the above-mentioned purpose, according to the first aspect of the present invention, there is provided a method for preparing a hard carbon negative electrode material, which comprises: S1, mixing a hard carbon precursor and a pore-forming agent in a mass ratio of 1:0.1-5 to obtain a precursor mixed material; S2, performing a preliminary carbonization on the precursor mixed material under protective gas protection at 200-800°C for 1-5 hours to obtain a preliminary carbonized material; S3, mixing the preliminary carbonized material with an acidic solution for 4-12 hours to obtain a template-removed material; S4, performing a second carbonization on the template-removed material at 1000-1200°C for 1-5 hours to obtain the hard carbon negative electrode material.

[0007] The preparation method of the present invention is to uniformly mix a hard carbon precursor and a pore former, first perform preliminary carbonization and pyrolysis at a relatively low temperature, and then remove the oxide template distributed on the surface of the carbon matrix through moderate acid washing. The oxide template distributed inside the carbon matrix remains inside the carbon matrix during a relatively short acid leaching time. During the second carbonization under a protective gas, the internal oxide template plays a role in etching the carbon matrix and thus increasing the closed-pore content, and the residual species from the reaction between the template and the carbon matrix are directly volatilized. The addition of the pore former increases the pore content in the hard carbon negative electrode material, increases the sodium storage sites, and improves the sodium storage capacity. By adjusting the content of the pore former, the acid leaching time, and the two-step carbonization temperature, the preparation method of the present invention can regulate the pore content.

[0008] In some preferred embodiments of the present invention, the hard carbon precursor includes one or a combination of two or more of cellulose, lignin, and sodium lignin sulfonate. These preferred precursors are easy to obtain and low in cost.

[0009] In some preferred embodiments of the present invention, the pore-forming agent includes a zinc salt; preferably, the pore-forming agent includes one or a combination of two or more of zinc gluconate, zinc lactate, zinc acetate, zinc propionate, zinc chloride, zinc sulfate, and zinc nitrate.

[0010] In some preferred embodiments of the present invention, the protective gas includes nitrogen, argon, or a combination of the two.

[0011] In some preferred embodiments of the present invention, the preliminary carbonization is carried out in a tube furnace at a heating rate of 1 to 5°C / min; preferably, the second carbonization is carried out in a tube furnace at a heating rate of 1 to 5°C / min. When the heating rate is higher than the above conditions, it is easy to cause insufficient pyrolysis of the precursor, while when it is lower than the above rate, it will lead to an increase in production time and energy consumption.

[0012] In some preferred embodiments of the present invention, the solute in the acidic solution includes one or a combination of two or more of hydrochloric acid, sulfuric acid, nitric acid, and phosphoric acid. Preferably, the concentration of the solute in the acidic solution is 1 mol / L; preferably, the mass ratio of the preliminary carbonized material to the acidic solution is 1:50 to 1:100.

[0013] In some preferred embodiments of the present invention, the preparation method further comprises: washing and drying the de-templated material, and then performing the second carbonization.

[0014] According to another aspect of the present invention, a hard carbon negative electrode material obtained according to the above preparation method is also provided.

[0015] According to another aspect of the present invention, a sodium ion battery negative electrode comprising the hard carbon negative electrode material is also provided. The method for preparing the negative electrode can be conventional in the art.

[0016] According to another aspect of the present invention, a sodium ion battery comprising the above sodium ion battery negative electrode is also provided. The method of assembling the battery can be conventional in the art. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 The 0.1C first-week charge and discharge diagram of the hard carbon negative electrode material prepared in Example 1 after assembling a half-cell and testing is shown.

[0018] Figure 2 The 0.1C first-week charge and discharge diagram of the hard carbon negative electrode material prepared in Comparative Example 1 after assembling a half-cell and testing is shown.

[0019] Figure 3 The XRD test pattern of the hard carbon negative electrode material prepared in Example 1 is shown. DETAILED DESCRIPTION

[0020] In order to have a clearer understanding of the technical features, purposes and beneficial effects of the present invention, the technical solution of the present invention is now described in detail below, but it should not be construed as limiting the applicable scope of the present invention.

[0021] Example 1

[0022] This embodiment provides a method for preparing a hard carbon negative electrode, comprising the following steps:

[0023] S1: Weigh 2 g of cellulose and 2 g of zinc gluconate, grind them thoroughly to make them evenly mixed, and obtain a precursor mixed material;

[0024] S2: Preliminary carbonization of the precursor mixed material in an argon atmosphere of a tube furnace at a temperature of 3°C / min up to 450°C for 1 hour to obtain a preliminary carbonized material;

[0025] S3: stirring the preliminary carbonized material in a 1 mol / L hydrochloric acid solution for 6 h to remove part of the template to obtain a de-templated material, wherein the mass ratio of the preliminary carbonized material to the acidic solution is 1:80;

[0026] S4: The washed and template-removed material is subjected to a second carbonization in an inert atmosphere of a tube furnace at a temperature of 3°C / min up to 1100°C for 1 hour to obtain a hard carbon negative electrode material.

[0027] The hard carbon material, superp conductive agent and PAA binder are mixed in a mass ratio of 8:1:1 to form a slurry; the slurry is coated on aluminum foil to form a negative electrode sheet; the electrode sheet and the sodium metal sheet are used as positive and negative electrodes respectively, the glass fiber filter paper is used as a diaphragm, and the electrolyte is 1M NaPF 6 The ethylene glycol dimethyl ether solution was assembled into a button battery in an argon atmosphere glove box and the charge and discharge test was carried out after standing for 12 hours. The test voltage range was 0.01V-2V and the 1C current density was 300mA / g.

[0028] In this embodiment, after the cellulose is subjected to a two-step pore-forming modification by moderate acid washing with a zinc gluconate-derived template and high-temperature etching, the prepared hard carbon has an increased pore content and an increased number of sodium storage sites, and has excellent sodium storage performance. The charge and discharge data of the first week at 0.1C are as follows: Figure 1 As shown in FIG. 1 , the first-week reversible capacity is 338 mAh / g and the first efficiency is 86.13%. The XRD pattern of the hard carbon negative electrode material obtained in Example 1 is shown in FIG. Figure 3 As shown by Figure 3 It can be seen that the material exhibits obvious broad derivative peaks at 22° and 43°, corresponding to the (002) and (100) crystal planes of hard carbon materials, and is a typical hard carbon material.

[0029] Example 2

[0030] This embodiment provides a method for preparing a hard carbon negative electrode, comprising the following steps:

[0031] S1: Weigh 2 g of cellulose and 2 g of zinc gluconate and grind them thoroughly to make them evenly mixed to obtain a precursor mixed material;

[0032] S2: Preliminary carbonization of the precursor mixed material in a tube furnace at 3°C / min to 450°C for 1 h in an argon atmosphere to obtain a preliminary carbonized material;

[0033] S3: The preliminary carbonized material is stirred in a 1 mol / L hydrochloric acid solution for 12 h to wash and remove part of the template to obtain a de-templated material, wherein the mass ratio of the preliminary carbonized material to the acidic solution is 1:80;

[0034] S4: The washed and template-removed material is subjected to a second carbonization in an inert atmosphere of a tube furnace at a temperature of 3°C / min up to 1100°C for 1 hour to obtain a hard carbon negative electrode material.

[0035] The hard carbon material, superp conductive agent and PAA binder are mixed in a mass ratio of 8:1:1 to form a slurry; the slurry is coated on aluminum foil to form a negative electrode sheet; the electrode sheet and the sodium metal sheet are used as positive and negative electrodes respectively, the glass fiber filter paper is used as a diaphragm, and the electrolyte is 1M NaPF 6The ethylene glycol dimethyl ether solution was assembled into a button battery in an argon atmosphere glove box and the charge and discharge test was carried out after standing for 12 hours. The test voltage range was 0.01V-2V and the 1C current density was 300mA / g.

[0036] In this embodiment, after cellulose is modified by a one-step pore-forming method using a zinc gluconate-derived template, the sodium storage capacity of the hard carbon prepared is improved, and its reversible capacity of charge and discharge in the first cycle at 0.1C is 324 mAh / g.

[0037] Example 3

[0038] This embodiment provides a method for preparing a hard carbon negative electrode, comprising the following steps:

[0039] S1: Weigh 3 g of cellulose and 1 g of zinc gluconate, grind them thoroughly to make them evenly mixed, and obtain a precursor mixed material;

[0040] S2: Preliminary carbonization of the precursor mixed material in a tube furnace under argon atmosphere at 3°C / min up to 450°C for 1h to obtain a preliminary carbonized material;

[0041] S3: The preliminary carbonized material is stirred in a 1 mol / L hydrochloric acid solution for 6 h for washing to remove part of the template agent to obtain a de-templated material, wherein the mass ratio of the preliminary carbonized material to the acidic solution is 1:80;

[0042] S4: The washed material is placed in a tube furnace in an inert atmosphere and heated to 1100° C. at 3° C. / min for a second carbonization for 1 h to obtain a hard carbon negative electrode material.

[0043] The hard carbon material, superp conductive agent and PAA binder are mixed in a mass ratio of 8:1:1 to form a slurry; the slurry is coated on aluminum foil to form a negative electrode sheet; the electrode sheet and the sodium metal sheet are used as positive and negative electrodes respectively, the glass fiber filter paper is used as a diaphragm, and the electrolyte is 1M NaPF 6 The ethylene glycol dimethyl ether solution was assembled into a button battery in an argon atmosphere glove box and the charge and discharge test was carried out after standing for 12 hours. The test voltage range was 0.01V-2V and the 1C current density was 300mA / g.

[0044] In this embodiment, due to the low content of the pore-forming agent, the sodium storage capacity of the prepared hard carbon is relatively low, which is 277 mAh / g.

[0045] Example 4

[0046] This embodiment provides a method for preparing a hard carbon negative electrode, comprising the following steps:

[0047] S1: Weigh 1 g of cellulose and 3 g of zinc gluconate and grind them thoroughly to make them evenly mixed to obtain a precursor mixed material;

[0048] S2: Preliminary carbonization of the precursor mixed material in a tube furnace under argon atmosphere at 3°C / min up to 450°C for 1h to obtain a preliminary carbonized material;

[0049] S3: stirring the preliminary carbonized material in a 1 mol / L hydrochloric acid solution for 6 h to remove part of the template to obtain a de-templated material, wherein the mass ratio of the preliminary carbonized material to the acidic solution is 1:80;

[0050] S4: The washed material is placed in a tube furnace in an inert atmosphere and heated to 1100° C. at 3° C. / min for a second carbonization for 1 h to obtain a hard carbon negative electrode material.

[0051] The hard carbon material, superp conductive agent and PAA binder are mixed in a mass ratio of 8:1:1 to form a slurry; the slurry is coated on aluminum foil to form a negative electrode sheet; the electrode sheet and the sodium metal sheet are used as positive and negative electrodes respectively, the glass fiber filter paper is used as a diaphragm, and the electrolyte is 1M NaPF 6 The ethylene glycol dimethyl ether solution was assembled into a button battery in an argon atmosphere glove box and the charge and discharge test was carried out after standing for 12 hours. The test voltage range was 0.01V-2V and the 1C current density was 300mA / g.

[0052] In this embodiment, due to the excessively high content of the pore-forming agent, the sodium storage capacity of the prepared hard carbon is relatively low, which is 258 mAh / g.

[0053] Comparative Example 1

[0054] This comparative example provides a method for preparing a hard carbon negative electrode, which comprises:

[0055] 4 g of cellulose was weighed and carbonized at 1100°C for 1 h in an argon atmosphere in a tubular furnace to obtain a cellulose-derived hard carbon material.

[0056] The hard carbon material, superp conductive agent and PAA binder are mixed in a mass ratio of 8:1:1 to form a slurry; the slurry is coated on aluminum foil to form a negative electrode sheet; the electrode sheet and the sodium metal sheet are used as positive and negative electrodes respectively, and the glass fiber separator and the electrolyte are 1M NaPF 6 The ethylene glycol dimethyl ether solution was assembled into a button battery in an argon atmosphere glove box and the charge and discharge test was carried out after standing for 12 hours. The test voltage range was 0.01V-2V and the 1C current density was 300mA / g.

[0057] In Comparative Example 1, since no pore-forming agent is added to the hard carbon material, the pore content in the derived hard carbon is small and the sodium storage sites are small, so the sodium storage capacity is low. Figure 2 As shown, the reversible charge capacity in the first week is 264 mAh / g.

[0058] The above description is only a specific embodiment of the present invention and cannot be used to limit the scope of the invention. Therefore, the replacement of equivalent components, or equivalent changes and modifications made according to the protection scope of the present invention should still fall within the scope covered by the present invention.

Claims

1. A method for preparing a hard carbon negative electrode material, It is characterized in that include: S1, mixing a hard carbon precursor and a pore former in a mass ratio of 1:0.1 to 5 to obtain a precursor mixed material; S2, preliminarily carbonizing the precursor mixed material under protective gas protection at 200-800° C. for 1-5 hours to obtain a preliminarily carbonized material; S3, mixing the preliminary carbonized material with an acidic solution for 4 to 12 hours to obtain a de-templated material; S4, subjecting the removed template material to a second carbonization at 1000-1200° C. for 1-5 hours to obtain the hard carbon negative electrode material.

2. The preparation method according to claim 1, It is characterized in that The hard carbon precursor includes one or a combination of two or more of cellulose, lignin, and sodium lignin sulfonate.

3. The preparation method according to claim 1, It is characterized in that The pore-forming agent includes zinc salt; preferably, the pore-forming agent includes one or a combination of two or more of zinc gluconate, zinc lactate, zinc acetate, zinc propionate, zinc chloride, zinc sulfate, and zinc nitrate.

4. The preparation method according to claim 1, It is characterized in that The protective gas includes nitrogen, argon or a combination of the two.

5. The preparation method according to claim 1, It is characterized in that The preliminary carbonization is carried out in a tubular furnace at a heating rate of 1 to 5° C. / min; preferably, the second carbonization is carried out in a tubular furnace at a heating rate of 1 to 5° C. / min.

6. The preparation method according to claim 1, It is characterized in that The solute in the acidic solution includes one or a combination of two or more of hydrochloric acid, sulfuric acid, nitric acid and phosphoric acid; preferably, the mass ratio of the preliminary carbonized material to the acidic solution is 1:50 to 1:

100.

7. The preparation method according to claim 1, It is characterized in that The preparation method further comprises: washing and drying the de-templated material, and then performing the second carbonization.

8. A hard carbon negative electrode material obtained by the preparation method according to any one of claims 1 to 7.

9. A sodium ion battery negative electrode comprising the hard carbon negative electrode material according to claim 8.

10. A sodium ion battery comprising the sodium ion battery negative electrode according to claim 9.

Citation Information

Cited By

  • Hard carbon negative electrode material and preparation method thereof, negative electrode and battery

    CN119735195A

  • Hard carbon negative electrode material, preparation method thereof, negative electrode and battery

    CN119735195B

  • Preparation method of biomass hard carbon negative electrode material of sodium ion battery

    CN119797325A

  • Preparation method of biomass hard carbon negative electrode material of sodium ion battery

    CN119797325B